Mayor Karen Humphrey Press Conference at Eaton Plaza re Running for Re-Election - Watkins, Howard::::::::: (1988)
Virginia Sanchez, Luisa Medina, Charles Francis at Karen Humphrey Press Conference in Eaton Plaza